Mini-cutting of hermaphrodite papaya 'Golden' with auxin inductor in semi-hydroponic system - Schmildt, Omar; Schmildt, Edilson Romais; Alexandre, Rodrigo Sobreira; Oliveira, Marcio José Vieira de; Ferreguetti, Geraldo Antônio; Nascimento, Adriel Lima; Santos, Karina Tiemi Hassuda dos (Revista de Ciências Agroveterinárias, 2019)
Papaya is traditionally propagated by seeds. Asexual propagation is an alternative for the production of hermaphrodite plants, with the fruit pattern required by the consumer market. The objective of this study was to study the vegetative propagation in 'Golden' hermaphrodite papaya, by testing the indole-3-butyric acid (IBA) in the rooting of mini-cuttings in a semi-hydroponic system. The experimental design was completely randomized. The treatments consisted of five concentrations of IBA (0, 3, 6, 9, and 12 mg L-1), with four replicates of six mini-cuttings taken from hermaphrodite plants in each plot. After 60 days of cultivation, the mini-cuttings were analyzed for rooting percentage, survival percentage, length of the largest root, and the number of leaves. The concentration around 9 mg L-1 of IBA provided a better induction to the rooting of mini-cuttings, as well as greater seedling survival, leaf formation, and root quality. The use of 9 mg L-1 of IBA in the semi-hydroponic system of seedling production is recommended using 'Golden' hermaphrodite papaya mini-cuttings.